Composite diaphragm as well as preparation method and application thereof
By using a multi-layer composite separator in quasi-solid-state lithium batteries, the problem of poor electrolyte locking and interface matching in quasi-solid-state lithium batteries is solved, and higher battery safety and energy density are achieved.
Patent Information
- Application Number
- CN202411317027.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
In quasi-solid lithium batteries, traditional separators have problems such as poor wetting, low adsorption and poor retention of the electrolyte, which leads to low battery safety and insufficient energy density, and poor matching with the lithium negative electrode, which makes the electrolyte unable to effectively lock.
The composite separator structure is adopted, including the first base film layer, the second base film layer and the sponge structure layer, the porosity is increased step by step, the gel electrolyte is filled, and a positive electrode material or an inorganic nanoparticle coating is provided on the side of the composite separator. To improve liquid retention and interface matching.
It improves the liquid retention capacity and interface humidity of the battery, reduces interface resistance, enhances the safety and circulation performance of the battery, and extends the service life of the battery.
Smart Images

Figure CN119208921A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a composite separator and a preparation method and application thereof. Background Art
[0002] With the development of science and technology, batteries will become the core of future high-tech development. Traditional batteries use organic liquid as electrolyte, which contains a large amount of organic solvents. It is easy to volatilize at high temperatures, has poor thermal stability, and is prone to combustion and fire, which is an important factor in the safety hazards of batteries. In order to improve the safety of lithium-ion batteries, researchers have gradually taken measures to reduce the use of organic electrolytes in lithium-ion batteries. The scientific community has proposed quasi-solid-state batteries, that is, the liquid content in the battery is 1-5wt%. From the existing technology, quasi-solid-state batteries, especially quasi-solid-state lithium batteries, have the advantages of high safety and a wide range of operating temperatures; and quasi-solid-state batteries have fast charging and discharging speeds and have the potential for high energy density. In response to this, researchers have invested more research on quasi-solid-state batteries. During this research process, the core component of the battery, the diaphragm, has become the key point for breakthrough technology.
[0003] Traditional diaphragm materials are mainly porous polyolefins, such as polyethylene (PE) and polyethylene / polypropylene (PE / PP) films. Although PP / PE and the like have many advantages in the application of batteries containing liquid electrolytes, these diaphragms have huge problems in the technical upgrade of quasi-solid-state batteries: ① The electrolyte has poor wettability, which is related to the interface wetting problem; and the adsorption amount is small, which is mainly due to leakage when the external part is damaged; the retention is poor, especially in the open system, there is a problem of electrolyte volatilization; this shortcoming is more prominent in quasi-solid-state batteries where the electrolyte only accounts for 1%-5%. ② For lithium batteries, a simple PP / PE film is easily punctured by lithium dendrites, resulting in a short circuit in the battery, which is prone to the risk of battery short circuit.
[0004] Based on the traditional membrane research, the scientific research community has proposed a membrane coating technology; the existing technologies include: ① Ceramic particle coated membrane: using the base membrane as the matrix, coating the surface with a layer of Al 2 O 3 、SiO 2 Mg(OH) 2Or other inorganic ceramic particles with excellent heat resistance, which are tightly bonded to the matrix after special processing;②PVDF coating: PVDF is polyvinylidene fluoride, a white powdery crystalline polymer. PVDF coated diaphragm has the characteristics of low internal resistance, high (thickness / porosity) uniformity, good mechanical properties, good chemical and electrical stability, etc.;③Aramid coated diaphragm Aramid fiber, as a high-performance fiber, has heat resistance that can withstand temperatures above 400°C and excellent fire retardancy, which can effectively prevent the fabric from melting when heated. The coating obtained by composite treatment with high heat-resistant aramid resin can greatly improve the heat resistance of the diaphragm, achieving a comprehensive combination of closed-cell characteristics and heat resistance.
[0005] However, as far as quasi-solid-state batteries are concerned, the electrolyte content in the battery is less than 5%, and the above-mentioned diaphragm coating method still has the following problems: First, although a quasi-solid-state battery can be obtained by the above-mentioned coating method, the amount of liquid retained in the battery is less, which will limit the improvement of lithium ion mobility, which is not conducive to the reduction of the internal resistance of the battery, nor is it conducive to the high-current charging and discharging of the battery; in the application of quasi-solid-state batteries, it will eventually lead to an increase in the internal resistance of the battery and a rapid decrease in the cycle performance. Secondly, the diaphragm obtained by the above method has poor matching with the negative electrode of the battery, especially it cannot be adapted to the lithium negative electrode. In the process of adapting to the lithium negative electrode, the electrolyte outside the diaphragm will continue to react negatively with the lithium negative electrode, and the SEI film (solid electrolyte interface film) will be continuously generated, while the lithium negative electrode and the electrolyte will be continuously consumed, and thus the lithium negative electrode cannot be adapted, thereby failing to improve the energy density of the battery.
[0006] In addition, some literature uses diatomaceous earth cavity shells to store electrolytes, but it cannot effectively lock the electrolytes; some literature uses electrospinning technology to composite inorganic nanoparticles and cellulose to obtain coated diaphragms, which also have the disadvantage of being unable to effectively lock the electrolytes. Summary of the invention
[0007] A technical problem to be solved by the present invention is how to provide a composite diaphragm and its preparation method and application, so that the prepared composite diaphragm can effectively lock the electrolyte and increase the liquid retention capacity; and can improve the interface wettability, reduce the interface resistance, have good matching with the negative electrode, and increase the safety of battery use.
[0008] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0009] According to the present invention, a composite diaphragm is provided, which comprises:
[0010] A first base film layer, comprising a first polymeric porous film; pores of the first polymeric porous film are filled with a gel electrolyte;
[0011] The second base film layer is disposed on the first base film layer; the second base film layer comprises a second polymeric porous film; the pores of the second polymeric porous film are filled with a gel electrolyte;
[0012] The sponge structure layer is arranged between the first basement membrane layer and the second basement membrane layer; the porosity of the sponge structure layer is greater than the porosity of the first basement membrane layer and the second basement membrane layer; and the pores of the sponge structure layer are filled with gel electrolyte.
[0013] Preferably, in the aforementioned composite diaphragm, the porosity K of the first basement membrane layer and the second basement membrane layer is 40-60%; the porosity K of the sponge structure layer is 1 is 50-80%; and, K1:K is 1.2-2; the pore size of the first basement membrane layer and the second basement membrane layer is less than 2 μm; the pore size of the sponge structure layer is less than 3 μm.
[0014] Preferably, in the aforementioned composite membrane, a positive electrode material coating is provided on one side of the composite membrane; and / or an inorganic nanoparticle coating is provided on the other side of the composite membrane.
[0015] Preferably, in the aforementioned composite separator, the positive electrode material is any one of lithium iron phosphate, lithium manganese oxide, ternary material NCM, and ternary material NCA.
[0016] Preferably, in the aforementioned composite diaphragm, the inorganic nanoparticles are one or more of aluminum oxide, titanium dioxide, silicon dioxide, and magnesium hydroxide.
[0017] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0018] According to the present invention, a method for preparing a composite diaphragm is provided, which comprises the following steps:
[0019] S1. Overlapping the two base films to form a double-layer film, dripping electrolyte in an inert gas atmosphere until the film is saturated with absorption; the two base films are polymer porous membranes;
[0020] S2. Heating causes the adjacent sides of the two basement membranes to adhere to each other to form a sponge structure layer, thereby obtaining a composite diaphragm that is in a gel state as a whole.
[0021] Preferably, the aforementioned preparation method further comprises the following steps:
[0022] Before step S1, a slurry is disposed on one side of a base film; the slurry contains a slurry of a positive electrode material or contains inorganic nanoparticles;
[0023] In step S1 , the slurry-free sides of two base films are overlapped.
[0024] Preferably, the aforementioned preparation method further comprises the following steps:
[0025] Before step S1, a slurry containing positive electrode material is disposed on one side of a base film, and a slurry containing inorganic nanoparticles is disposed on one side of another base film;
[0026] In step S1 , the slurry-free sides of two base films are overlapped.
[0027] Preferably, in the aforementioned preparation method, the electrolyte is a lithium salt; and the amount of the electrolyte added is 0.04 to 0.06 mL per square centimeter of the double-layer membrane.
[0028] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0029] An embodiment of the present invention also provides an application of the aforementioned composite diaphragm in a quasi-solid-state battery.
[0030] By means of the above technical solution, the composite diaphragm and its preparation method and application proposed by the present invention have at least the following beneficial effects:
[0031] 1. The composite diaphragm prepared by the present invention is provided with a first base film layer and a second base film layer, and the pores of the first polymer porous film in the first base film layer and the second polymer porous film in the second base film layer are filled with gel electrolyte; a sponge structure layer is provided between the first base film layer and the second base film layer, and since the porosity of the sponge structure layer is greater than that of the first base film layer and the second base film layer; therefore, the sponge structure layer stores more electrolyte per unit volume, which helps to improve the electrolyte retention capacity of the composite diaphragm; the increase in the retention capacity also helps to improve the interface wettability between the composite diaphragm and the positive and negative electrodes of the battery, reduce the interface resistance, have good matching with the negative electrode, and increase the safety of the battery. Moreover, the sponge structure layer is sandwiched by the first base film layer and the second base film layer, which can avoid the direct outflow of a large amount of electrolyte stored in the sponge structure layer and the impact on the positive and negative electrodes of the battery, improve the safety of the battery, and extend the service life of the battery.
[0032] 2. The composite diaphragm of the present invention can be provided with a positive electrode material coating on one side, corresponding to the positive electrode of the battery, which helps to reduce the interface resistance between the positive electrode and the electrolyte interface; it can also be provided with an inorganic nanoparticle coating on one side, corresponding to the negative electrode of the battery, which helps to make the composite diaphragm better match the negative electrode of the battery.
[0033] 3. The present invention provides a method for preparing a composite diaphragm, which comprises directly taking two polymer porous membranes as base membranes, overlapping the sides of the base membranes to form a double-layer membrane body; then dripping an electrolyte into the double-layer membrane body in an inert gas atmosphere until the membrane body is saturated with absorption; then, heating is performed to make the adjacent sides of the two base membranes adhere to each other to form a sponge structure layer, and the base membranes and the electrolyte are both converted into a gel state, and finally a composite diaphragm in a gel state as a whole is obtained; the composite diaphragm prepared by the present invention comprises a first base membrane layer, a sponge structure layer, and a second base membrane layer; since the sponge structure layer is formed by the adhesion between the adjacent sides of the base membranes The sponge structure layer is formed, and its porosity is higher than that of each base film layer, and the storage capacity of the electrolyte per unit volume is greater. Moreover, the sponge structure layer also helps to enhance the effective sealing and preservation of the gel electrolyte stored inside it, thus helping to improve the liquid retention of the composite diaphragm; more importantly, since the sponge structure layer is formed by adhesion between the adjacent sides of the base film, the sponge structure layer has better fluidity with the first base film layer and the second base film layer, so that the composite diaphragm prepared by the present invention reduces or even avoids the generation of interface resistance between the film layer and / or the structure layer, which helps to improve the electrochemical energy such as the cycle performance of the battery. In addition, the two base films used in the preparation method can be commercially used polypropylene (PP) diaphragms, polyethylene (PE) films, and composite films superimposed by polypropylene (PP) films and polyethylene (PE) films, so the preparation method is simple and easy to industrialize.
[0034] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is the capacity retention rate of the batteries prepared in Example 1, Example 8 and Comparative Example 1. DETAILED DESCRIPTION
[0036] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of a composite diaphragm and its preparation method and application proposed in accordance with the present invention, its specific implementation method, structure, characteristics and effects, in combination with the accompanying drawings and preferred embodiments.
[0037] The present invention provides a composite diaphragm, which comprises:
[0038] A first base film layer, comprising a first polymeric porous film; pores of the first polymeric porous film are filled with a gel electrolyte;
[0039] The second base film layer is disposed on the first base film layer; the second base film layer comprises a second polymeric porous film; the pores of the second polymeric porous film are filled with a gel electrolyte;
[0040] The sponge structure layer is arranged between the first basement membrane layer and the second basement membrane layer; the porosity of the sponge structure layer is greater than the porosity of the first basement membrane layer and the second basement membrane layer; and the pores of the sponge structure layer are filled with gel electrolyte.
[0041] In the composite diaphragm of the present invention, the first base film layer, the sponge structure layer and the second base film layer are sequentially stacked and arranged in parallel, and the porosity of the sponge structure layer is greater than that of the first base film layer and the second base film layer. Therefore, in the sponge structure layer, the electrolyte stored in the unit volume is more than that of the first base film layer and the second base film layer, which helps to increase the average liquid retention per unit volume of the composite diaphragm; the increase in liquid retention also helps to increase the interfacial wettability between the composite diaphragm and the positive and negative electrodes of the battery, reduce the interface resistance, and have good matching with the negative electrode, thereby increasing the safety of battery use. Moreover, since the sponge structure layer is clamped by the first base film layer and the second base film layer, the sponge structure layer does not contact the positive and negative electrodes of the battery during use of the composite diaphragm provided by the present invention, thereby avoiding a large amount of electrolyte stored in the sponge structure layer from partially flowing out and directly contacting the positive and negative electrodes of the battery to consume the positive and negative electrodes of the battery; thereby helping to improve the safety of the battery and extend the service life of the battery.
[0042] In some embodiments, the first polymeric porous membrane and the second polymeric porous membrane are made of the same material; in other embodiments, the first polymeric porous membrane and the second polymeric porous membrane are made of different materials.
[0043] In some embodiments, the gel electrolyte filled in the pores of the first polymer-based porous membrane, the gel electrolyte filled in the pores of the second polymer-based porous membrane, and the gel electrolyte filled in the pores of the sponge structure layer are all the same substance.
[0044] Preferably, in the above technical solution, the porosity K of the first basement membrane layer and the second basement membrane layer is 40-60%; the porosity K of the sponge structure layer is 1 is 50-80%; and, K 1 :K is 1.2~2; the pore size of the first base membrane layer and the second base membrane layer is less than 2μm; the pore size of the sponge structure layer is less than 3μm. Under this condition, the pores of the sponge structure layer can not only store a large amount of electrolyte, but also effectively seal and preserve the electrolyte. Moreover, the first base membrane layer and the second base membrane layer that clamp the sponge structure layer can further effectively seal and preserve the electrolyte stored in the sponge structure layer, thereby preventing part of the large amount of electrolyte stored in the sponge structure layer from flowing out and directly contacting the positive and negative electrodes of the battery, thereby consuming the positive and negative electrodes of the battery, thereby avoiding affecting the electrochemical performance and service life of the battery.
[0045] Preferably, in the aforementioned technical solution, the thickness of the sponge structure layer is 2 to 50 μm; further preferably, the thickness of the sponge structure layer is 10 to 30 μm; strictly limiting the thickness of the sponge structure layer can enable the sponge structure layer to not only store a large amount of gel electrolyte, but also help to make the prepared composite diaphragm lighter and thinner for easy use.
[0046] In some embodiments, the overall thickness of the composite membrane prepared by the present invention does not exceed 100 μm; preferably, the overall thickness of the composite membrane does not exceed 80 μm; further preferably, the overall thickness of the composite membrane does not exceed 60 μm; further preferably, the overall thickness of the composite membrane does not exceed 50 μm.
[0047] Preferably, in the aforementioned technical solution, the first base membrane layer, the sponge structure layer and the second base membrane layer are materials with the same or similar components, so as to reduce or even avoid the generation of interface resistance between the membrane layers and / or structure layers, which helps to improve the electrical properties of the battery, such as the cycle performance.
[0048] Preferably, in the aforementioned technical solution, a positive electrode material coating is provided on one side of the composite membrane; and / or an inorganic nanoparticle coating is provided on the other side of the composite membrane.
[0049] In some embodiments, a positive electrode material coating is disposed on the side of the first base film layer away from the second base film layer; and / or an inorganic nanoparticle coating is disposed on the side of the second base film layer away from the first base film layer. In other embodiments, a positive electrode material coating is disposed on the side of the first base film layer away from the second base film layer; and / or an inorganic nanoparticle coating is disposed on the side of the second base film layer away from the first base film layer.
[0050] In some embodiments, the positive electrode material in the positive electrode material coating is any one of lithium iron phosphate, lithium manganese oxide, ternary material NCM, and ternary material NCA. The ternary material NCM refers to a combination of nickel (NI), cobalt (CO) and manganese (Mn), and the ternary material NCA refers to a combination of nickel (NI), cobalt (CO) and aluminum (Al).
[0051] In some embodiments, the inorganic nanoparticles in the inorganic nanoparticle coating are one or a mixture of aluminum oxide, titanium dioxide, silicon dioxide, and magnesium hydroxide.
[0052] The present invention also provides a method for preparing a composite diaphragm, which comprises the following steps:
[0053] S1. Overlapping the two base films to form a double-layer film, dripping electrolyte in an inert gas atmosphere until the film is saturated with absorption; the two base films are polymer porous membranes;
[0054] S2. Heating causes the adjacent sides of the two basement membranes to adhere to each other to form a sponge structure layer, thereby obtaining a composite diaphragm that is in a gel state as a whole.
[0055] The two base films of the present invention can be regarded as single-layer films, so the film layer can be regarded as having only two side surfaces. After the two base film side surfaces are superimposed and overlapped, the double-layer film body as a whole can also be regarded as having only two side surfaces in contact with the outside world.
[0056] In some embodiments, the electrolyte is prepared by dissolving a lithium salt in an organic solvent; the lithium salt may be lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium iodide (LiI), lithium fluoride (LiF) or more.
[0057] In some embodiments, the organic solvent in which the lithium salt is dissolved is a carbonate organic solvent; preferably, the carbonate organic solvent is one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC).
[0058] Preferably, in the above technical solution, the lithium salt concentration in the electrolyte is 0.2-3 mol / kg; strictly limiting the lithium salt concentration in the electrolyte is conducive to enhancing the electrical properties of the prepared composite diaphragm. If the lithium salt concentration in the electrolyte is too high, waste will occur; if the lithium salt concentration is too low, the electrical properties of the prepared composite diaphragm will be reduced.
[0059] The said adding electrolyte until the membrane is saturated with absorption means that during the process of adding electrolyte, the pore structure of the double-layer membrane is fully filled with electrolyte; the gap on the sides where the two base membranes are superimposed and overlapped (hereinafter referred to as "base membrane gap") is fully filled with electrolyte. When the above purpose is achieved, the membrane is saturated with electrolyte.
[0060] In the process of dripping electrolyte into the double-layer membrane body of the present invention, the inert gas forming the inert gas atmosphere is not specifically limited, as long as it does not react with the electrolyte. In some embodiments, the gas of the inert gas atmosphere provided by the present invention is one or more of helium, neon, argon, krypton, and xenon. Adding electrolyte in an inert gas atmosphere can not only prevent the electrolyte from being oxidized during the dripping process; but also prevent the storage of gas between the two base films and the gap between the base films, so as to avoid affecting the absorption and storage of electrolyte by the membrane body; therefore, using an inert gas atmosphere during the process of dripping electrolyte can also help to increase the adsorption and storage capacity of the double-layer membrane body for electrolyte.
[0061] The present invention heats the double-layer membrane body that has been saturated with electrolyte in step S2. Since both base membranes are polymer porous membranes, each base membrane further generates intramolecular or intermolecular crosslinking during the heating process, each base membrane swells, and the electrolyte also swells, thereby forming a gel-state base membrane and electrolyte; and adhesion occurs between the adjacent sides of the two base membranes. Under appropriate heating conditions, the adjacent sides of the two base membranes adhere to form a sponge structure layer to increase the effective sealing and preservation of the electrolyte stored between the base membranes, and finally form a composite diaphragm that is in a gel state as a whole. Since the sponge structure layer is formed by adhesion between the adjacent sides of the base membranes, the sponge structure layer has better fluidity with the first base membrane layer and the second base membrane layer. Therefore, the composite diaphragm prepared by the present invention reduces or even avoids the generation of interface resistance between the membrane layer and / or structure layer, which helps to improve the electrical properties of the battery such as the cycle performance.
[0062] In some embodiments, the two base films of the present invention can be selected from commercially available polypropylene (PP) diaphragms, polyethylene (PE) films, and composite films of polypropylene (PP) films and polyethylene (PE) films. The two base films can be the same or different. This makes the preparation method of the present invention simple and easy to industrialize.
[0063] Preferably, in some embodiments of the aforementioned technical solution, before step S1, slurry is provided on a single side of a base film, and then the slurry-free sides of two base films are overlapped; the slurry contains positive electrode material or inorganic nanoparticles.
[0064] Further preferably, in some other embodiments, before step S1, a slurry is disposed on one side of a base film; the slurry contains positive electrode material or inorganic nanoparticles.
[0065] The present invention arranges slurry on the side of the base film before step S1, so that during the process of dripping the electrolyte, the slurry can fully absorb the electrolyte, thereby improving the preservation of the electrolyte by the composite diaphragm.
[0066] The method for preparing the slurry containing the positive electrode material of the present invention is as follows:
[0067] The first organic polymer and the positive electrode material are mixed uniformly to form a mixture A; the first conductive agent is added to the mixture A and mixed uniformly to form a mixture B; the mixture B is heated under a first temperature condition and stirred to be uniformly dispersed in the mixed solvent a to form a first suspension; the mixed solvent a is formed by mixing the first organic solvent and water.
[0068] In some embodiments, the first organic polymer is one or more of polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0069] In some embodiments, the mass ratio of the first organic polymer to the positive electrode material is 1:(0.3~3); preferably, the mass ratio of the first organic polymer to the positive electrode material is 1:3 to 3:1; strictly limiting the mass ratio of the first organic polymer to the positive electrode material helps the prepared composite membrane to effectively reduce the interface resistance.
[0070] The present invention firstly mixes the first organic polymer and the positive electrode material uniformly to form a mixture A, and then further adds the first conductive agent to the mixture A, which helps the first organic polymer and the positive electrode material to mix uniformly, and further helps the prepared composite separator to effectively reduce the interface resistance. The present invention avoids the technical solution of directly adding the first organic polymer, the positive electrode material and the first conductive agent to the mixture in no particular order, so as to avoid uneven mixing of the first organic polymer and the positive electrode material, so as to avoid the prepared composite separator from failing to effectively reduce the interface resistance.
[0071] In some embodiments, the mass percentage of the first conductive agent in the mixture B is 1-5%.
[0072] In some embodiments, the first organic solvent in the mixed solvent a is acetone, isopropanol, or a mixture of the two; and the water is deionized water.
[0073] Preferably, in the aforementioned technical solution, the mass ratio (wt%) of the first organic solvent to water is 80:20 to 98:2. Under this condition, the dispersion system of the mixture B in the mixed solvent a is more stable.
[0074] In some embodiments, the present invention is heated at a first temperature of 40 to 80°C, and during the heating process, the mixture B is added to the mixed solvent a while stirring, and then stirred for 1 to 6 hours to form a first suspension; when the suspension system is observed to be stable and no stratification occurs, a slurry containing a positive electrode material is formed. Strictly limiting the process conditions for mixing the mixture B and the mixed solvent a to form the first suspension helps the first suspension to form quickly, and the formed first suspension has good uniform dispersion performance.
[0075] The method for preparing the slurry containing inorganic nanoparticles of the present invention is as follows:
[0076] The second organic polymer and the inorganic nanoparticles are mixed uniformly to form a mixture C; the second conductive agent is added to the mixture C and mixed uniformly to form a mixture D; heating under a second temperature condition and stirring to make the mixture D uniformly dispersed in the mixed solvent b to form a second suspension; the mixed solvent b is formed by mixing the second organic solvent and water.
[0077] In some embodiments, the second organic polymer is one or more of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene.
[0078] The first organic polymer and the second organic polymer may be the same substance or different substances.
[0079] In some embodiments, the mass ratio of the second organic polymer to the inorganic nanoparticles is 1:(0.3-3); preferably, the mass ratio of the second organic polymer to the inorganic nanoparticles is 1:3 to 3:1; under this condition, it helps the prepared composite separator to better match the battery negative electrode.
[0080] In order to make the second organic polymer and the inorganic nanoparticles mix evenly, the present invention first mixes the second organic polymer and the inorganic nanoparticles, and then further adds the second conductive agent after the mixing is evenly performed; this helps the second organic polymer and the inorganic nanoparticles to mix more evenly, so that the prepared composite separator can effectively match the battery negative electrode.
[0081] In some embodiments, the mass percentage of the second conductive agent in the mixture D is 1-5%.
[0082] The mass percentage of the first conductive agent in mixture B and the mass percentage of the second conductive agent in mixture D may be the same or different.
[0083] In some embodiments, the first conductive agent and the second conductive agent are one or more of graphite conductive agent, conductive carbon black, graphene, and metal powder; the graphite conductive agent includes one or more of KS-6, KS-15, SFG-6, and SFG-15. The conductive carbon black includes one or more of acetylene black, Super P, Super S, 350G, carbon fiber VGCF, carbon nanotubes CNTs, Ketjen black, and activated carbon.
[0084] The first conductive agent and the second conductive agent may be the same material or different materials.
[0085] In some embodiments, the second organic solvent in the mixed solvent b is acetone, isopropanol or a mixture of the two, and the water is deionized water.
[0086] The second organic solvent may be the same as or different from the first organic solvent.
[0087] Preferably, in the aforementioned technical solution, the mass ratio (wt%) of the second organic solvent to water is 80:20 to 98:2. Under this condition, the dispersion system of the mixture D in the mixed solvent b is more stable.
[0088] The mass ratio of the second organic solvent to water may be the same as or different from the mass ratio of the first organic solvent to water.
[0089] In some embodiments, the present invention is heated under the condition of a second temperature of 40 to 80°C, and during the heating process, the mixture D is added to the mixed solvent b while stirring, and then stirred for 1 to 6 hours to form a second suspension; when the suspension system is observed to be stable and no stratification occurs, a slurry containing inorganic nanoparticles is formed. Strictly limiting the process conditions for mixing the mixture D with the mixed solvent b to form the first suspension helps the second suspension to form quickly, and the formed suspension has good uniform dispersion performance.
[0090] The first temperature condition and the second temperature condition may be the same or different.
[0091] The method of setting the first slurry and / or the second slurry on one side of the base film of the present invention is to cover the one side of the first base film or the second base film by coating, spin coating, scraping, spraying, etc. The present invention does not limit the device or tool for achieving the above-mentioned slurry covering method, as long as the above-mentioned covering effect can be achieved.
[0092] Preferably, in the aforementioned technical solution, during the preparation process, if the first slurry and / or the second slurry is set on a single side of the base film, during the process of dripping the electrolyte, it is also necessary to ensure that the first slurry and / or the second slurry covered on the side of the double-layer film body fully absorbs the electrolyte; and the inert gas forming the inert gas atmosphere does not react with the slurry.
[0093] Preferably, in the aforementioned technical solution, in the process of dripping the electrolyte into the double-layer film body, 0.04 to 0.06 mL of the aforementioned electrolyte is dripped per square centimeter of the double-layer film body. It should be noted that, since the film layer of the base film used in the present invention is thin, when calculating the amount of electrolyte dripped, the double-layer film body is regarded as the entire film layer, and the thickness of the film layer is ignored, and the amount of electrolyte dripped is calculated based on the area of a single side of the double-layer film body. The present invention strictly limits the amount of electrolyte dripped, which not only enables the slurry coating covering the side of the double-layer film body to fully absorb the electrolyte, but also enables the pore structure of the two base films and the gap between the base films to be fully filled with the electrolyte, and finally enables the double-layer film body as a whole to be saturated with the electrolyte; and it can also avoid the waste of electrolyte. In addition, strictly limiting the amount of electrolyte added can also avoid affecting the degree of adhesion between the adjacent surfaces of the two basement membranes (i.e., the overlapping surfaces). The limited range of the amount of electrolyte added in the present invention is conducive to the adhesion of the adjacent surfaces of the two basement membranes to form a sponge structure layer, and the formed sponge structure layer can not only store a large amount of gel electrolyte, but also effectively seal and preserve the gel electrolyte, thereby increasing the liquid retention capacity of the composite diaphragm.
[0094] Preferably, in the aforementioned technical solution, the heating temperature of the double-layer membrane body saturated with electrolyte absorption is 50-100°C, and the heating time is 1-3h. Under this condition, the adjacent sides of the two base films undergo intramolecular or intermolecular crosslinking during the heating process, so that the adjacent sides adhere to each other to form a sponge structure layer, so that the two base films are more tightly bonded and the double-layer membrane body is better integrated; further, under this condition, the sponge structure layer formed can not only store a large amount of gel electrolyte, but also further enhance the effective sealing and preservation of the gel electrolyte; the slurry on the side of the double-layer membrane body, the double-layer membrane body and the electrolyte stored therein swell, and the double-layer membrane body gradually gels and integrates under the action of heating, and finally forms a composite diaphragm in the form of a gel as a whole. The composite diaphragm obtained by the preparation method of the present invention is conducive to the effective sealing and preservation of the electrolyte; and improves the liquid retention of the electrolyte. If the heating temperature is too high and the heating time is too long, it is easy to increase the volatilization of the electrolyte stored in the double-layer membrane body, thereby reducing the electrolyte retention in the composite diaphragm; and, if the heating temperature is too high, the performance of the organic material will be reduced, the pore size of the base film layer is large, and the composite diaphragm formed has a low degree of blocking and preserving the gel electrolyte, affecting its electrolyte retention; and, it is also possible that part of the electrolyte will flow out of the diaphragm, consuming the positive and negative electrodes of the battery, which is not only not conducive to extending the service life of the battery, but may even cause safety hazards. If the heating temperature is too low, the slurry set on the side of the double-layer membrane body, the electrolyte stored in the double-layer membrane body, and the swelling degree of the base film are not enough, and the sponge structure layer may not be formed, or the porosity of the formed sponge structure layer is too high, the pore size is large, and the sponge structure layer has a low degree of effective blocking and preservation of the electrolyte stored inside; ultimately, the prepared composite diaphragm has a low electrolyte retention, and more electrolyte will flow out of the diaphragm, consuming the positive and negative electrodes of the battery, which is not conducive to extending the service life of the battery, and the safety hazards are more serious. In addition, when the heating temperature is too low, a sponge structure layer cannot be formed between the base membranes or the pore size of the formed sponge structure layer is too large, the battery prepared with the composite diaphragm will produce interface resistance, affecting the battery's electrical properties such as cycle performance.
[0095] Preferably, in the aforementioned technical solution, the thickness of the slurry set on the single side of the two base films is 20 to 100 μm. Strictly limiting the thickness of the slurry set on the single side of the base film helps the slurry covered on the sides of the two base films to swell into a gel state under the aforementioned heating conditions, thereby helping to improve the sealing and preservation of the electrolyte by the composite diaphragm, so that the electrical performance of the battery obtained by using the composite diaphragm prepared by the present invention is improved; and the generation of interface resistance between the composite diaphragm and the positive and negative electrodes of the battery is reduced or even avoided.
[0096] Preferably, the aforementioned technical solution can adjust the thickness of the prepared composite diaphragm by adjusting the coating layer of the base film and the content of the electrolyte dripped into the double-layer film body.
[0097] In some embodiments, the slurry thickness of the two base films is the same; in other embodiments, the slurry thickness of the two base films is different.
[0098] The present invention does not specifically limit the device used for heating in the preparation method or step, as long as the heating purpose can be achieved. The device used for stirring and the stirring conditions are also not specifically limited, as long as stirring can be implemented and the mixture is evenly dispersed in the mixed solvent.
[0099] The present invention also provides application of the composite diaphragm in a quasi-solid-state battery.
[0100] Preferably, in the aforementioned technical solution, the positive electrode of the battery corresponds to the side of the coating containing the positive electrode material of the composite diaphragm, which helps to reduce the interface resistance between the positive electrode of the battery and the electrolyte interface.
[0101] Preferably, in the aforementioned technical solution, the negative electrode of the battery corresponds to the side of the composite diaphragm containing the inorganic nanoparticle coating; this helps the composite diaphragm to better match the negative electrode of the battery, and the composite diaphragm is fully suitable for quasi-solid-state batteries.
[0102] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0103] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0104] Example 1
[0105] This embodiment prepares a composite diaphragm and a quasi-solid battery, and the specific operation steps are as follows:
[0106] 1) Preparation of slurry containing positive electrode material
[0107] PVDF-HFP and lithium iron phosphate are mixed in a mass ratio of 1:1, and mixed evenly to form a mixture A; conductive carbon black is added to the mixture A, and mixed evenly to form a mixture B; wherein the mass percentage of the conductive carbon black in the mixture B is 3%. Under the condition of heating temperature of 50°C, the mixture B is added to the mixed solvent a while stirring; the mixed solvent a is formed by mixing acetone and deionized water, and the acetone: deionized water = 90:10 (wt%); continue stirring for 2 hours; and form a suspension. When no stratification phenomenon is observed in the suspension, it is ready.
[0108] 2) Preparation of slurry containing inorganic nanoparticles
[0109] PVDF-HFP and nano-alumina particles are mixed at a mass ratio of 1:1, and the mixture C is obtained after being mixed evenly; conductive carbon black is added to the mixture C, and the mixture D is formed; wherein the mass percentage of the conductive carbon black in the mixture D is 3%. Under the condition of heating temperature of 50°C, the mixture D is added to the mixed solvent b while stirring; and the mixed solvent b is formed by mixing acetone and deionized water, acetone: deionized water = 90:10 (wt%); stirring is continued for 2 hours; a suspension is formed. When no stratification phenomenon is observed in the suspension, it is ready.
[0110] 3) Slurry coating
[0111] The slurry prepared in step 1) was coated on a PP separator (referred to as the first base film) using a doctor blade coater, and the coating thickness was 50 μm.
[0112] The slurry prepared in step 2) was coated on a second PP diaphragm (referred to as the second base film) using a blade coating machine, and the coating thickness was 50 μm.
[0113] 4) Gluing
[0114] The unscratched coating sides of the two PP diaphragms treated with slurry in step 3) are overlapped to form a double-layer membrane. In an argon atmosphere, 1 mol / kg of LiTFSI (EC / DMC=7:3) electrolyte is added to the double-layer membrane; 0.05 mL of electrolyte is dripped per square centimeter of the double-layer membrane. Further, the double-layer membrane saturated with electrolyte is heated at a heating temperature of 60°C for 1 hour, and the basement membrane gap of the double-layer membrane is tightly combined, and the whole is in a gel state, that is, a composite gel diaphragm is obtained.
[0115] The prepared diaphragm is subjected to longitudinal swelling test, porosity and pore size test, and liquid retention test, and the method is as follows:
[0116] Diaphragm longitudinal swelling test: The longitudinal swelling of the diaphragm was tested using a laser displacement sensor. The results are shown in Table 1.
[0117] Porosity and pore size detection of the diaphragm: The porosity detector and pore size analyzer were used for detection respectively. The results are shown in Table 1.
[0118] Liquid retention test: The composite diaphragm prepared in this example was divided into two portions, each of 10 g, and placed in the air and in a sealed vial for observation, and the remaining mass of the composite diaphragm was tested regularly. The test time and test results are shown in Table 2.
[0119] Preparation of quasi-solid batteries
[0120] With lithium iron phosphate as the positive electrode and lithium sheet as the negative electrode, the composite diaphragm prepared in this embodiment is used, and a button battery is prepared using a CR2032 battery shell by a lamination method to form a 30 mm × 50 mm soft-pack battery. The prepared quasi-solid battery is tested for interface resistance and cycle performance, and the test method is as follows:
[0121] a. Interface resistance test: The cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) of the battery prepared above were tested using an electrochemical workstation, and then the Zview software was used to simulate the solid-state battery, and finally the interface resistance of the battery was obtained.
[0122] b. Cyclic performance test. The battery prepared above was charged at 0.2C (current density of 0.15 mA / cm 2 ) at a constant current of 4.2 V, and then at a constant voltage of 0.05C cutoff for 500 cycles.
[0123] The interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0124] Example 2
[0125] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0126] 1) In the process of preparing the slurry containing the positive electrode material, the mass percentage of the conductive carbon black in the mixture B is 5%; the acetone:deionized water in the mixed solvent a is 85:15 (wt%); the heating temperature is 70° C., and the heating time is 3 hours.
[0127] 2) In the process of preparing the slurry containing inorganic nanoparticles, the mass percentage of conductive carbon black in the mixture D is 5%; the acetone:deionized water in the mixed solvent b is 85:15 (wt%), the heating temperature is 60° C., and the heating time is 4 hours.
[0128] 3) During the slurry coating process, the first base film is a PP diaphragm, and the second base film is a PE diaphragm; and the coating thickness of the slurry of the first base film and the second base film is 60 μm.
[0129] 4) During the gelation process, 0.06 mL of electrolyte was added per square centimeter of the double-layer membrane; then the membrane was heated at 80° C. for 2 hours to obtain a composite gel separator.
[0130] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0131] Example 3
[0132] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0133] 1) In the process of preparing the slurry containing the positive electrode material, PVDF-HFP and lithium iron phosphate are mixed in a mass ratio of 1:3; the mass percentage of conductive carbon black in the mixture B is 1%; acetone: deionized water in the mixed solvent a = 80:20 (wt%), the heating temperature is 40°C, and the heating time is 1 hour.
[0134] 2) In the process of preparing the slurry containing inorganic nanoparticles, PVDF-HFP and nano-alumina particles are mixed in a mass ratio of 1:3; the mass percentage of conductive carbon black in mixture B is 1%; acetone: deionized water in the mixed solvent b = 80:20 (wt%), the heating temperature is 40°C, and the heating time is 1 hour.
[0135] 3) During the slurry coating process, the coating thickness of the first base film and the second base film slurry is 20 μm.
[0136] 4) During the gelation process, 0.04 mL of electrolyte was added per square centimeter of the double-layer membrane; the mixture was heated at 50° C. for 1 hour to obtain a composite gel separator.
[0137] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0138] Example 4
[0139] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0140] 1) In the process of preparing the slurry containing the positive electrode material, PVDF-HFP and lithium iron phosphate are mixed in a mass ratio of 3:1; the mass percentage of conductive carbon black in the mixture B is 5%; acetone: deionized water in the mixed solvent a = 98:2 (wt%), the heating temperature is 80°C, and the heating time is 6 hours.
[0141] 2) In the process of preparing the slurry containing inorganic nanoparticles, PVDF-HFP and nano-alumina particles are mixed in a mass ratio of 3:1; the mass percentage of conductive carbon black in mixture B is 5%; acetone: deionized water in the mixed solvent b = 98:2 (wt%), the heating temperature is 80°C, and the heating time is 6 hours.
[0142] 3) During the slurry coating process, the coating thickness of the first base film and the second base film slurry is 100 μm.
[0143] 4) During the gelling process, the mixture is heated at 100° C. for 3 hours to obtain a composite gel membrane.
[0144] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0145] Example 5
[0146] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0147] 1) In the process of preparing the slurry containing the positive electrode material, PVDF-HFP and lithium iron phosphate are mixed in a mass ratio of 1:3; acetone: deionized water in the mixed solvent a = 80:20 (wt%), the heating temperature is 60° C., and the heating time is 3 hours.
[0148] 2) In the process of preparing the slurry containing inorganic nanoparticles, PVDF-HFP and nano-alumina particles are mixed in a mass ratio of 3:1; the mass percentage of conductive carbon black in the mixture B is 5%; the heating temperature is 50° C. and the heating time is 2 hours.
[0149] 3) During the slurry coating process, the coating thickness of the first base film slurry is 50 μm; the coating thickness of the second base film slurry is 40 μm.
[0150] 4) During the gelling process, the heating temperature is then set at 80° C. for 2 hours to obtain a composite gel membrane.
[0151] The prepared diaphragm was subjected to a longitudinal swelling degree test; the porosity and pore size of the diaphragm were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0152] Example 6
[0153] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0154] 1) In the process of preparing the slurry containing the positive electrode material, PVDF-HFP and lithium manganate are mixed in a mass ratio of 1:1; graphene is added to the formed mixture A; the mixed solvent a is formed by mixing isopropanol and deionized water, and isopropanol:deionized water=85:15 (wt%).
[0155] 2) In the process of preparing the slurry containing inorganic nanoparticles, titanium dioxide and PVDF-HFP are mixed in a mass ratio of 1:1; graphene is added to the formed mixture C; the mixed solvent b is formed by mixing isopropanol and deionized water, and isopropanol:deionized water=85:15 (wt%).
[0156] The prepared composite gel diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0157] Example 7
[0158] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0159] 1) In the process of preparing the slurry containing the positive electrode material, PVDF and lithium manganese oxide are mixed in a mass ratio of 1:3.
[0160] 2) In the process of preparing the slurry containing inorganic nanoparticles, titanium dioxide and PVDF-HFP are mixed in a mass ratio of 1:1; graphene is added to the formed mixture C; the mixed solvent b is formed by mixing isopropanol and deionized water, and isopropanol:deionized water=85:15 (wt%).
[0161] The prepared composite gel diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0162] Example 8
[0163] The preparation method of this embodiment is basically the same as that of Embodiment 1, with the difference that: the first base film is not subjected to slurry treatment, and only the second base film is subjected to slurry treatment, and the side of the second base film that has been subjected to slurry treatment and does not contain slurry is overlapped with the first base film, and the subsequent process steps are the same as those of Embodiment 1.
[0164] The prepared composite gel diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0165] Example 9
[0166] The preparation method of this embodiment is basically the same as that of Embodiment 1, with the difference that: the second base film is not subjected to slurry treatment, and only the first base film is subjected to slurry treatment, and the side of the first base film that has been subjected to slurry treatment and does not contain slurry is overlapped with the second base film, and the subsequent process steps are the same as those of Embodiment 1.
[0167] The prepared composite gel diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0168] Example 10
[0169] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that the first slurry does not contain positive electrode material, and the second slurry does not contain nano-alumina particles.
[0170] The prepared composite gel diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0171] Comparative Example 1
[0172] The preparation method of this comparative example is basically the same as that of Example 1, except that no heating is performed in the final gelling step.
[0173] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0174] Comparative Example 2
[0175] The preparation method of this comparative example is basically the same as that of Example 1, except that: during the slurry coating process, this comparative example takes a diaphragm as a base membrane and coats the first slurry and the second slurry on both sides thereof respectively; and the diaphragm used in this comparative example is from the same batch as the diaphragm used in Example 1.
[0176] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0177] Comparative Example 3
[0178] The preparation method of this comparative example is basically the same as that of Example 1, except that during the gelling process, the heating temperature is 30°C.
[0179] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0180] Comparative Example 4
[0181] The preparation method of this comparative example is basically the same as that of Example 1, except that during the gelling process, the heating temperature is 150°C.
[0182] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0183] Comparative Example 5
[0184] The preparation method of this comparative example is basically the same as that of Example 1, with the difference that: during the slurry coating process, this comparative example uses a diaphragm as the base membrane, and coats the first slurry and the second slurry on both sides thereof respectively; but the thickness of the diaphragm is the sum of the thicknesses of the two diaphragms in Example 1; the material and shape and size of the diaphragm are exactly the same as those of the two diaphragms used in Example 1.
[0185] The prepared diaphragm was subjected to a longitudinal swelling test; the porosity and pore size were tested, and the liquid retention capacity was tested; the method was the same as in Example 1, and the test results are shown in Tables 1 and 2; the prepared quasi-solid battery was subjected to an interface resistance test and a lithium cycle stability test, the method was the same as in Example 1, the interface resistance test results are shown in Table 3, and the lithium cycle stability test results are shown in Table 4.
[0186] Table 1 Properties of the diaphragms prepared in Examples and Comparative Examples
[0187]
[0188] Table 2. Test results of liquid retention capacity of diaphragms prepared in Examples and Comparative Examples
[0189]
[0190]
[0191] Note: When the diaphragm liquid retention is 9.50g, the outside of the diaphragm appears dry.
[0192] Table 3. Test results of interface resistance of quasi-solid batteries prepared in Examples and Comparative Examples
[0193] Group <![CDATA[Anode interface resistance (Ω / cm 2 )]]> <![CDATA[Negative electrode interfacial resistance (Ω / cm 2 )]]> Example 1 2.0 4.3 Example 2 1.9 4.2 Example 3 1.9 4.1 Example 4 1.9 4.3 Example 5 1.9 4.2 Example 6 2.0 4.2 Example 7 1.9 4.3 Example 8 15.0 4.3 Example 9 5.6 4.2 Example 10 13.6 4.2 Comparative Example 1 90.0 120.0 Comparative Example 2 95.0 128.0 Comparative Example 3 20.0 40 Comparative Example 4 15.0 36 Comparative Example 5 83.0 106.0
[0194] Table 4. Cyclic performance test results of quasi-solid batteries prepared in Examples and Comparative Examples
[0195]
[0196]
[0197] It can be seen from Examples 1-10 and Tables 1-4 that the present invention adopts two base films, which are superimposed and overlapped to form a double-layer film body, and an electrolyte is dripped into the double-layer film body until the double-layer film body is saturated with the electrolyte, and then further heated to form a gel-state composite diaphragm, and its volume longitudinal swelling range is 40 to 43 μm; and within the observation period of 100 days, the prepared composite diaphragm, whether stored in the air or in a closed system, the electrolyte of the composite diaphragm did not dry up, and the liquid retention amount was greatly increased; therefore, the composite diaphragm prepared by the present invention effectively seals and preserves the electrolyte, and the liquid retention amount is increased.
[0198] Combining Examples 1 to 10 and Tables 1 to 4, it can be seen that the preparation method of the present invention is adopted, and a coating containing positive electrode material is provided on a single side of the composite diaphragm, corresponding to the positive electrode of the battery, which helps to reduce the interface resistance between the positive electrode and the electrolyte interface, and the prepared quasi-solid battery cycle performance still has a capacity retention rate of 96% after 500 cycles; a coating containing inorganic nanoparticles is provided on a single side of the composite diaphragm, corresponding to the negative electrode of the battery, which helps to make the composite diaphragm better match the negative electrode of the battery, and the battery cycle performance is good. The side of the composite diaphragm contains a coating containing positive electrode material and an inorganic nanoparticle coating, and the interface resistance of the prepared battery positive electrode is less than 2Ω / cm 2 ; Negative electrode interface resistance is less than 4.5Ω / cm 2 , the battery electrical performance is good.
[0199] From the analysis of the comparative examples and the embodiments, it can be known that in the preparation method of the composite diaphragm provided by the present invention, if no heating is performed during the gelling process, or the heating temperature is lower than 50°C, or the heating temperature is higher than 100°C, the prepared composite diaphragm has low electrolyte retention and poor electrical properties. The reasons are as follows: if no heating is performed during the gelling process, the heating temperature is lower than 50°C, and the double-layer membrane body cannot be transformed into a gel state; the degree of adhesion between the adjacent sides of the first basement membrane and the second basement membrane is low, and the pore size of the sponge layer structure formed is 3 to 5 μm, and the porosity is greater than 80%, the sponge structure layer cannot effectively seal and preserve the electrolyte inside it, the gel electrolyte is easy to volatilize, and the electrical properties of the battery are also affected; moreover, the pore size of the sponge structure layer formed is large, part of the electrolyte will flow out, consuming the positive and negative electrodes of the battery, affecting the life of the battery, and the battery may generate interface resistance during the application of the composite diaphragm, affecting the cycle performance of the battery. If the heating temperature is too high, the pore size of the first base film layer and the second base film layer is 2-3μm, the performance of the organic material is reduced, the composite diaphragm has a low degree of effective sealing and preservation of the stored gel electrolyte, and the amount of electrolyte retained is reduced, which in turn affects the electrical performance of the battery. Comparative Example 1 does not heat during the gelation process, so the double-layer membrane does not undergo gel state conversion, and the longitudinal swelling degree is 0; Comparative Example 3 has a low heating temperature during the gelation process, so the electrolyte swelling degree in the double-layer membrane is low, the adjacent sides of the two base films have low adhesion, the sponge structure layer formed is loose, and the longitudinal swelling degree of the prepared diaphragm is significantly lower than that of the embodiment; Comparative Example 4 has a too high heating temperature, the performance of the organic material is reduced, and the prepared composite diaphragm has a reduced amount of electrolyte retention. Since the composite membranes prepared in Comparative Examples 1, 3, and 4 have a weak degree of sealing and preserving the electrolyte, the electrolyte in the composite membranes is easily volatilized in the air system; the electrolyte in the composite membrane prepared in Comparative Example 1 is completely dried up in less than 10 days in the air, and is also completely dried up in 100 days in a closed system; the electrolyte in the composite membrane prepared in Comparative Example 3 is completely dried up in less than 50 days in the air, and is almost dried up in 100 days in a closed system; the composite membrane prepared in Comparative Example 4 also has a significantly lower liquid retention capacity than that of the embodiment. Combined with Tables 1 to 4, the attached Figure 1 It can be seen that the capacity retention rate of comparative example 1 dropped to 91% at 200 cycles, and the capacity dropped to less than 50% at 300 cycles, and the battery stopped after 500 cycles. There are two main reasons for this: 1) the electrolyte that was not adsorbed by the diaphragm reacted with the negative electrode; 2) the electrolyte dried up.
[0200] From the analysis of Comparative Example 2 and the embodiment, it can be seen that if only a single base film is used, the liquid retention capacity of the prepared composite diaphragm is significantly reduced compared with the embodiment, and the longitudinal swelling degree is significantly lower than that of the embodiment; in the air system, the electrolyte is completely dried up in less than 100 days, and in the closed system at 100 days, the electrolyte is also close to drying up. The reason is that during the dripping of electrolyte in Comparative Example 2, since Comparative Example 2 cannot form a base film gap like the embodiment, during the dripping of electrolyte, the storage capacity of the double-layer membrane body for the electrolyte is significantly reduced, thereby significantly reducing the electrolyte retention capacity in the composite diaphragm.
[0201] In combination with Tables 1 to 4, it can be seen from the embodiment and comparative example 5 that only increasing the thickness of the base film cannot form a base film gap as in the embodiment, nor form the sponge structure layer of the present invention. During the process of dripping the electrolyte, the storage capacity of the double-layer membrane body for the electrolyte is significantly reduced; the electrolyte retention capacity in the composite diaphragm is low, and the electrical performance of the correspondingly prepared battery is also affected.
[0202] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0203] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A composite diaphragm, characterized in that: It includes: A first base film layer, comprising a first polymeric porous film; The pores of the first polymer porous membrane are filled with a gel electrolyte; The second base film layer is disposed on the first base film layer; the second base film layer comprises a second polymeric porous film; the pores of the second polymeric porous film are filled with a gel electrolyte; The sponge structure layer is arranged between the first basement membrane layer and the second basement membrane layer; the porosity of the sponge structure layer is greater than the porosity of the first basement membrane layer and the second basement membrane layer; and the pores of the sponge structure layer are filled with gel electrolyte.
2. The composite diaphragm according to claim 1, characterized in that: The porosity K of the first basement membrane layer and the second basement membrane layer is 40-60%; the porosity K1 of the sponge structure layer is 50-80%; and K1:K is 1.2-2; The pore sizes of the first basement membrane layer and the second basement membrane layer are less than 2 μm; the pore size of the sponge structure layer is less than 3 μm.
3. The composite diaphragm according to claim 2, characterized in that: One side of the composite membrane is provided with a positive electrode material coating; and / or the other side of the composite membrane is provided with an inorganic nanoparticle coating.
4. The composite diaphragm according to claim 3, characterized in that: The positive electrode material is any one of lithium iron phosphate, lithium manganese oxide, ternary material NCM, and ternary material NCA.
5. The composite diaphragm according to claim 3, characterized in that: The inorganic nanoparticles are one or more of aluminum oxide, titanium dioxide, silicon dioxide and magnesium hydroxide.
6. A method for preparing a composite diaphragm, characterized in that: It includes the following steps: S1. Overlapping the two base films to form a double-layer film, dripping electrolyte in an inert gas atmosphere until the film is saturated with absorption; the two base films are polymer porous membranes; S2. Heating causes the adjacent sides of the two basement membranes to adhere to each other to form a sponge structure layer, thereby obtaining a composite diaphragm that is in a gel state as a whole.
7. The preparation method according to claim 6, characterized in that: It also includes the following steps: Before step S1, a slurry is disposed on one side of a base film; the slurry contains positive electrode material or inorganic nanoparticles; In step S1 , the slurry-free sides of two base films are overlapped.
8. The preparation method according to claim 6, characterized in that: It also includes the following steps: Before step S1, a slurry containing positive electrode material is disposed on one side of a base film, and a slurry containing inorganic nanoparticles is disposed on one side of another base film; In step S1 , the slurry-free sides of two base films are overlapped.
9. The preparation method according to claim 8, characterized in that: The electrolyte is a lithium salt; the amount of the electrolyte added is 0.04 to 0.06 mL per square centimeter of the double-layer membrane.
10. Use of the composite separator according to any one of claims 1 to 5 in a quasi-solid-state battery.
